Rancangan Bigbook Bilingual dalam Konteks Budaya Jawa Barat - Yona Wahyuningsih; Nono Harsono; Setyaningsih Setyaningsih (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This research is the background of the phenomenon of cultural crisis that should be resolved Cultural Preservation in the form of efforts to protect, develop and utilize a dynamic culture. It is not only the global problem that triggers cultural amnesia but individual self-factors that should be aware of and action among elementary school children that is happy with foreign cultures such as cinema, reading books, food and appearance styles have become the development of the current modern era. This study aims to describe the development, implementation and identify the difficulties faced by students in the development of Big Book as a tool for developing media literacy for elementary school children in the cultural context of West Java. Regional coverage in West Java which is the subject of analysis is Bogor, Sukabumi, Cianjur, Bandung, Karawang, Subang, Sumedang, Garut, Tasikmalaya, Kuningan and Cirebon.